RIRI STORY BOOKS: SEBUAH UPAYA MENINGKATKAN PENGETAHUAN, EMOSI SOSIAL, DAN MINAT TERHADAP SASTRA ANAK DI MASA PENDEMI - Nasifatul syarifah; Khaerunnisa (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
The pandemic causes children to be unable to socialize and develop their knowledge and social emotions to the fullest. One of the efforts to continue to increase knowledge and social emotions in children is through reading containing children's literature. One of the media for reading children's literature is Riri Story Books. as a reading medium, this application has several features and content that can increase children's interest in reading literature. This study used descriptive qualitative method. The use of this method is considered very appropriate because the research data will be described descriptively using words. To obtain research data, researchers used the method of observation, interviews, and literature study. Some of these data collection techniques are considered very appropriate because they support qualitative research designs and help researchers obtain research data more easily. In this study, the theory of the criteria for illustrated stories was used to determine the type and criteria of media for reading children's stories that were appropriate to be used during the pandemic. This study aims to provide information and knowledge related to the media for reading children's literature during the pandemic so that children can still receive content that helps them adapt to the pandemic. Keywords: pandemic, children's literature, picture stories, media, riri story books